1999
DOI: 10.1029/98jd02303
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation in the equatorial free troposphere: Favorable environments during PEM‐Tropics

Abstract: Abstract. A combination of aerosol and gas phase instrumentation was employed aboard the NASA-P3B as part of the Pacific Exploratory Mission-Tropics (PEM-T) in the eastern equatorial Pacific during August-October 1996. Recent particle production was found in cloudprocessed air over extended regions aloft (6-8 km). These were clearly associated with clean marine air lofted by deep convection and scavenged of most aerosol mass in the Intertropical Convergence Zone (ITCZ) and in more aged cloud-scavenged air infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 34 publications
10
122
1
Order By: Relevance
“…11), with maximum concentrations simulated in the upper troposphere (UT), as has been observed in recent field campaigns (e.g., Clarke et al, 1999) and simulated in models (Adams and Seinfeld, 2002). Simulated UT concentrations in the tropics peak at higher concentrations and at higher altitudes than at mid latitudes.…”
Section: Global Cn and Ccn Distributionsmentioning
confidence: 68%
“…11), with maximum concentrations simulated in the upper troposphere (UT), as has been observed in recent field campaigns (e.g., Clarke et al, 1999) and simulated in models (Adams and Seinfeld, 2002). Simulated UT concentrations in the tropics peak at higher concentrations and at higher altitudes than at mid latitudes.…”
Section: Global Cn and Ccn Distributionsmentioning
confidence: 68%
“…The entrainment of aerosols from the FT into the MBL may provide a source of aerosols in the MBL (Raes, 1995;Clarke et al, 1998b;Raes et al, 2000). Clarke (1992) and Clarke et al (1998bClarke et al ( , 1999 reported, based on the experiments on the upper-tropospheric aerosol, new particles and sulfuric acid concentrations in the FT. Weber and McMurry (1996) also reported aerosol size distribution in the FT based on the observations at Mauna Loa Observatory. Their results suggest that the aerosol concentration in the FT shows a consistent shape.…”
Section: Mbl-ft Exchangementioning
confidence: 99%
“…Dickerson et al, 1987;Poulida et al, 1996). Since outflow of larger convective clouds has recently been suggested as a source for new particles, UCN measurements have been widely used to detect convective outflow (de Reus et al, 2001;Clarke et al, 1999;Wang et al, 2000). Three events during which the trace gas signatures indicate transport of boundary layer air into or above the tropopause region are marked in grey in Figs.…”
Section: Meteorological Situationmentioning
confidence: 99%